2020
DOI: 10.1109/access.2020.3023040
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 3D Virtual “Try-On” on Online Sales and Customers’ Purchasing Experiences

Abstract: The advancement of the Internet and technology has made it possible to purchase and use different types of products and services online instead of offline. In particular, as the scale of online shopping malls is rapidly increasing, new functions have been tried and introduced to compensate for the limitation of not being able to directly wear clothes in an online mall. Among them, 3D virtual try-on is an innovative service and its technology is being advanced with continuous interest. Technological advances an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 35 publications
0
12
0
2
Order By: Relevance
“…Such cognitive deviation will cause consumers' psychological discomfort, which will then encourage their behavioral tendency to reduce the sense of dissonance and to cancel the purchase decision (Lee, 2015). Virtual try-on technology has the potential to replace physical fitting rooms, and previous studies have shown that virtual try-on can be an effective marketing tool and can significantly reduce the return rate (Hwangbo et al ., 2020). Augmented reality (AR) technology has value in retail applications such as clothing, cosmetics and furniture, where consumers can use virtual trials to increase the certainty of purchase decisions and help reduce return rates (Perannagari and Chakrabarti, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Such cognitive deviation will cause consumers' psychological discomfort, which will then encourage their behavioral tendency to reduce the sense of dissonance and to cancel the purchase decision (Lee, 2015). Virtual try-on technology has the potential to replace physical fitting rooms, and previous studies have shown that virtual try-on can be an effective marketing tool and can significantly reduce the return rate (Hwangbo et al ., 2020). Augmented reality (AR) technology has value in retail applications such as clothing, cosmetics and furniture, where consumers can use virtual trials to increase the certainty of purchase decisions and help reduce return rates (Perannagari and Chakrabarti, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study conducted on virtual dressing room applications found that Kinect for Windows can generate a perfect fit of clothing to suit customers' requirements (Musry & Al-Jabi, 2019). With the technological revolution, e-retailers install the websites the features so that the consumers can create 3D (three-dimensional) virtual models corresponding to their physical features (Cho & Schwarz, 2012;Hwangbo et al, 2020;Merle et al, 2012). While the early VTO was based on avatar-orphoto-based, recent development included augmented-reality based, which enriches the consumers' experience of reality and significantly impacts consumer purchase-making decisions (Beck & Crié, 2018;Hilken et al, 2018).…”
Section: Attitude Towards Vto As a Mediatormentioning
confidence: 99%
“…With escalating interest in VTO services, many fashion companies look forward to making unique attempts to expand their businesses to e‐commerce and introduce 3‐D technology to improve the quality (Debbabi et al, 2010). Furthermore, as the recent hit global pandemic increased customers' reluctance to engage in face‐to‐face contact and prefer e‐buying, the number of companies making this VTO available is increasing (Hwangbo et al, 2020; Papagiannidis et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…where d jj ðZÞ represents the function of the boundary volume of indoor scene model elements and d x ðx i , x j Þ represents the color component value of indoor scene state information [16,17]. Binary segmentation is used for processing, the visual transfer is carried out in the virtual scene, and the virtual reality imaging of indoor space is segmented again.…”
Section: Interior Optimization Design Based On 3d Visual Graphics Ren...mentioning
confidence: 99%